Evaluasi Pemilihan Supplier Besi Pada PT.XYZ Menggunakan Metode Analytical Network Process (ANP) Dan Technique For Others Preference By Similarity To Ideal Solution (TOPSIS) - Rafid Amarullah (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2024)
PT. XYZ is one of the developer companiesProperty. In this study, the Analytical method was usedNetwork Process (ANP) and Technique For Others methodsPreferences by Similarity to Ideal Solution (TOPSIS) inRespond to supplier evaluation problems that occur incompany. Based on the results of the study, it was obtainedthe ranking of each criterion. On the price criterion consists of H1(0.262), H4 (0.261), H5 (0.244), and H2 (0.233). Atquality criteria consist of K3 (0.384), K4 (0.377